Relationships between sex appeal, attitude towards advertisement, brand and purchase intention on luxury fashion - Zahari, Nurfareena (2019)
Despite the recent economic downturn, luxury fashion industry remains as one of the most profitable industries worldwide. This is because consumers are having higher purchase intention and willing to consume luxury fashion brands and goods than ever before. The growth of sales in emerging economies has surpassed the mature economies, which make them as the most attractive market for luxury fashion industry. This scenario also includes Malaysia which is one of the most attractive markets in Asian regions. Although luxury fashion marketers frequently adopt sex appeal as their major selling technique, little research has been conducted in regards to sex appeal in luxury fashion advertising. This is ironic given a large number of luxury fashion houses that adopt sex appeal in their advertising. The degrees of sex appeal such as low, medium and high can affect attitudes, which inadvertently influence purchase intention. This study will take an initiative to identify the relationship between sex appeal, attitude towards advertisement, brand and purchase intention featuring “Dolce & Gabbana” in Malaysia. Data from a survey of 160 of local postgraduate students at Universiti Putra Malaysia (UPM) were gathered and analysed by using Confirmatory Factor Analysis (CFA), Analysis of Variance (ANOVA) and Regression analysis. The study finds that the degrees of sex appeal have significant effects on both attitude towards the advertisement and the brand but not purchase intention. It was found that the low degree of sex appeal generated the most favourable attitude towards the advertisement and the brand, followed by the medium and the high degree of sex appeal. The medium degree of sex appeal generated only a slightly lower favourable attitude towards the advertisement and the brand than the low degree of sex appeal. Finally, attitude towards the advertisement and brand have significant positive relationships with purchase intention. The findings of this study provide an overview and clearer vision of the relationship between the degrees of sex appeal, attitude towards advertisement and brand and purchase intention on luxury fashion in Malaysia. Limitations and recommendations for future research are highlighted.